PPRT selection technique using analytical hierarchy process - Mohamad, Mohd Sharif (2010)
When making a selection for numbers of application which is done manually without any help from any systematic technique, it may raise an issue of accuracy, precise and biasness. In the PPRT application, the selection and evaluation are done manually. In this project, a technique based on Analytical Hierarchy Technique (AHP) is designed and developed in order to make an evaluation and selection of PPRT application. The aim is to ensure the selection process is more precise, accurate and can avoid any biasness issue. This technique is studied and designed based on the poverty assessment technique from district offices in Melaka, Malaysia. A hierarchical indexes are designed based on the criteria that been used in the official form of PPRT application. A number of 23 samples of data which had been endorsed by Ex co of Melaka state are used to test this technique. Furthermore the comparison of those two method are given in this paper. All the calculations of this technique are done in a software called Expert Choice version 11.5 to get the result of grading for all the samples. The result of this technique shows that there are three (3) samples that are not qualify. The developed technique also satisfies in term of ease of accuracy and preciseness but need a further study due to some limitation as explained in the recommendation of this paper